Intelligent Healthcare System using a Machine learning model to Predict Diseases - Stanley G, *Sharun T, *Satheesh Kumar B, Muthamil Sudar K, Nagaraj.P (International Journal of Advanced Science and Technology, 2020)
One of the most emerging technologies in recent times is Machine Learning. Machine Learning techniques provide various algorithms and machine learning models which helps machines to understand the problems and derive solutions for the particular problem. We are also using this machine learning techniques to create a model which helps us in the prediction of diseases. We are using Logistic Regression algorithm in our machine learning model. We are using this machine learning model which excels in analysing the given symptoms and predicting the diseases. We are creating a user-friendly webpage which gets the input from the user and after receiving the inputs it converts these inputs as test datasets and runs in our machine learning model. Then the predicted output is then displayed in the webpage as output. The output is also shows the severity of the disease and predicts which stage of the disease the user may be. Our model can be used to predict various diseases based on the users requirement. We are using Logistic Regression instead of Linear Regression to avoid the chances of overfitting or underfitting which may lead to inaccurate predictions.There are number of algorithms and program to detect one disease at a time, but we are creating an application which option to predict various diseases at the same page.